Long-Term Results of Mini-Monoka® Monocanalicular Intubation in the Repair of Canalicular Lacerations - Armida L. Suller, MD; Alexander D. Tan, MD (Philippine Journal of Ophthalmology)
Objective: To report the epidemiology of canalicular lacerations and surgical outcomes of canalicular laceration repair with Mini-Monoka® (FCI Ophthalmics, Issy-les-Moulineaux, Cedex, France) intubation.